Domain Matched Epitaxial Growth of BaSrTiO3 thin films on Al2O3 - A. A. Odinets; A. V. Tumarkin (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The model of the crystal epitaxial growth of multicomponent films on single crystal substrates with domain corresponds are presented to an example of a solid solution of barium strontium titanate on sapphire substrates (r-cut). Domain matched epitaxial growth involves the matching of the film and substrate lattice planes having a similar structure, by matching domains. Varying the component composition of the solid solution allows to change the domain size in the range sufficient to reduce the mismatch of the lattice of barium strontium titanate and sapphire. Thus, it is possible to design an epitaxial film growth of various solid solutions on single-crystal substrates.